The effects of body weight and age on performance, egg quality, blood parameters, and economic production of laying hens - Ekinci, O; Esenbuga, N; Dagdemir, V (Journal of the Hellenic Veterinary Medical Society, 2023)
This study was conducted to investigate the effects of body weight on performance, egg quality, blood parameters, and economics of production of Lohmann white laying hens. A total of 288 Lohmann white layers, 44 wks of age, were allocated randomly to three groups, each formed 24 replicate cages as subgroups, comprising of four hens. The study was conducted over a period of 36 wks. Feed and water were offered ad libitum in the experiment. Performance parameters were significantly affected by body weight except for cracked egg. Considering the egg production, differences among the groups were significant (P<0.001). Egg production in the light group was higher than that of the medium and the heavy group. However, egg weight was determined to be lower in the light group (66.58 g) than in medium (67.54 g) and heavy hens (68.84 g). Hens in light body weight had lower feed intake and feed conversion ratio (FCR) than hens in heavy body weight. There were no alterations in egg quality parameters in response to increased body weight except for SS and yolk color. SS decreased linearly (P<0.001) and YC increased with BW. Other egg quality parameters did not change as BW increased. There was no change in the metabolic profile in response to increased BW except for glucose. Heavy hens had greater serum glucose concentrations than light and medium hens. This study emphasized that body weight affected the laying performance, some egg quality parameters, but had no significant effect on metabolic profile except for glucose. As a result, it was found that there was a positive relationship between the egg weight and the body weight of the hens. In this case, it is possible to produce more eggs with less feed by increasing the number of light and medium-weight chickens in the herd for profitable livestock.